2010
DOI: 10.1161/hypertensionaha.109.135772
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren Monotherapy Does Not Cause Paradoxical Blood Pressure Rises

Abstract: Abstract-Angiotensin receptor blockers, angiotensin-converting enzyme inhibitors, and diuretics all cause reactive rises in plasma renin concentration, but particularly high levels have been reported with aliskiren. This prompted speculation that blockade of plasma renin activity with aliskiren could be overwhelmed, leading to paradoxical increases in blood pressure. This meta-analysis of data from 4877 patients from 8 randomized, double-blind, placebo-and/or activecontrolled trials examined this hypothesis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…6) Aliskiren inhibits the renin-angiotensin (Ang) system at the rate-limiting step by reducing plasma renin activity and thereby prevents the formation of Ang I and II. The renin-angiotensin system (RAS) plays an integral part in the regulation of BP.…”
Section: )mentioning
confidence: 99%
“…6) Aliskiren inhibits the renin-angiotensin (Ang) system at the rate-limiting step by reducing plasma renin activity and thereby prevents the formation of Ang I and II. The renin-angiotensin system (RAS) plays an integral part in the regulation of BP.…”
Section: )mentioning
confidence: 99%
“…Notably, none of the 536 patients in whom PRA was measured and who received aliskiren (300 mg) exhibited an increase in systolic BP greater than 10 mm Hg or in diastolic BP greater than 5 mm Hg accompanied by an increase in PRA greater than 0.1 ng/mL per hour. The authors concluded that the incidence of "paradoxical" BP increases with aliskiren was similar to that seen during treatment with other drugs, and that BP elevation was not related to increased PRA [16].…”
Section: Implications Of the Reactive Rise In Plasma Renin Concentrationmentioning
confidence: 83%
“…Stanton et al [16] conducted a meta-analysis involving 4877 patients from eight aliskiren trials with placebo controls, active controls, or both. The incidence of paradoxical BP increases following at least 4 weeks of treatment with aliskiren (300 mg), high-dose ARBs (irbesartan, 300 mg; losartan, 100 mg; valsartan, 320 mg), ramipril (10 mg), HCTZ (25 mg), or placebo was determined.…”
Section: Implications Of the Reactive Rise In Plasma Renin Concentrationmentioning
confidence: 99%
“…The 'prohypertensive' hypothesis has not been shown in trials reporting on aliskiren efficacy in various populations [Menard and Azizi, 2007;Stanton et al 2010]. In contrast, aliskiren monotherapy has been shown to reduce blood pressure regardless of the PRA levels [Schmieder et al 2009;Stanton et al 2009].…”
Section: Paradoxical Effect Of Direct Renin Inhibitionmentioning
confidence: 99%